2017
DOI: 10.1259/bjr.20160898
|View full text |Cite
|
Sign up to set email alerts
|

Effect of total lung capacity, gender and height on CT airway measurements

Abstract: √WAPi10, WT and WT are different in males and females. WT and WT are correlated with height in females only but not with TLC or in males. Advances in knowledge: CT airway measurements are influenced by gender and by height in females only but not by TLC. They should be adjusted according to gender and height in females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Quantitative CT metrics of airways include the study of wall thickness, area and density, and lumen diameter and area. However, its use faces a certain number of limitations, as airway metrics are highly influenced by lung volume, aging and inflammation [ 60 ]. Therefore, applying airway metrics in clinical practice is still at the preliminary stage.…”
Section: The Role Of Radiomics In Lung Diseasesmentioning
confidence: 99%
“…Quantitative CT metrics of airways include the study of wall thickness, area and density, and lumen diameter and area. However, its use faces a certain number of limitations, as airway metrics are highly influenced by lung volume, aging and inflammation [ 60 ]. Therefore, applying airway metrics in clinical practice is still at the preliminary stage.…”
Section: The Role Of Radiomics In Lung Diseasesmentioning
confidence: 99%
“…We also compared the virtual 3D reconstructions of the KNM-WT 15000 thoraces (juvenile and adult) with the modern human reference sample using measured maximum width, depth and height. We calculated total lung capacity of the KNM-WT 15000 reconstructed thoraces following the methods presented in García-Martínez et al 54 , but we included a male sample only (Supplementary Table 1; n = 40; mean age, 21 years; mean stature, 180.37 cm; mean total lung capacity (TLC), 7.77 l) 72 and compared these values to published reference data 73 . Thoracic spine length was used to estimate the stature of KNM-WT 15000 in juvenile and adult individuals following Nagesh and Pradeep Kumar 74 (Supplementary Table 6).…”
Section: Growth Simulations and Analyses Of The Knm-wt 15000 Thoraxmentioning
confidence: 99%
“…Quantitative analysis of the airway follows the preliminary processing step of bronchial tree segmentation and isolation of three-dimensional airway model 89,90 (Figure 4a-c). Airway is usually quantified according to its generation, and the generation-specific mean can be calculated throughout the entire lung, 91 nonetheless, Gupta et al reported that a single bronchus might be representative. 92 Direct characterization of airway is feasible for several bronchial generations, 93 yet, direct QCT metrics are widely accepted up to fifth generation.…”
Section: Airway Quantificationmentioning
confidence: 99%
“…The variability and potential bias of airway metrics are significant and include lung volume, age and transient inflammation. 91,97 For this reason, the clinical application of airway QCT is still to be validated. 4 Pi10 is deemed the most consistent among airway metrics, albeit only when calculated on a minimum of 12 subsegmental bronchi.…”
Section: Airway Quantificationmentioning
confidence: 99%